(NrELQTIWISTSKIE NELINEJNYE \FFEKTY W PLAZME (B/s - (NcINCADZE(B, (NnODAR lEWANOWI^s; (NcHAKAQ(B, (NdEWI dAWIDOWI^s; (NiNSTITUT FIZIKI an gssrs ((NtBILISI (B:s (NmECNIEREBA(B,s, 1989)
(NbIBLIOGR(B.: (NS(B. 166-172 (166 (NNAZW(B.)s
(NbIBLIOGR(B.: (NS(B. 166-172s
Keywords: (NpLAZMA (B((NFIZ(B.)s -- (NwOLNOWYE PROCESSYs; (NpLAZMA (B((NFIZ(B.)s -- (N|LEKTROMAGNITNYE SWOJSTWAs